Analisis Tingkat Kesehatan Bank dengan Menggunakan Metode Risk-Based Bank Rating (RBBR) pada PT. Bank Mega Syariah Periode Tahun 2017-2021 - Rian Dani; Iqra Wiarta (Yayasan Literasi Sains Indonesia, 2022)
This study analyzes the health level of banks using the Risk-Based Bank Rating (RBBR) method. The secondary data used in this study was taken from the Financial Statements of PT Bank Mega Syariah on the official website of PT Bank Mega Syariah for the period 2017-2021. The Risk-Based Bank Rating (RBBR) method based on BI Circular No. 13/24/DPNP uses Risk Profile, Earning and Capital assessments. The method used in this research is descriptive research method with a quantitative approach. The results show that the Risk Profile component calculated using the NPF ratio in 2017 was 2.75 percent, in 2018 it was 1.96 percent, in 2019 it was 1.49 percent, in 2020 it was 1.38 percent and in 2021. by 0.97 percent. In addition, the FDR ratio in 2017 was 91.05 percent, in 2018 it was 90.88 percent, in 2019 it was 94.53 percent, in 2020 it was 63.94 percent, and in 2021 it was 62.84 percent. In the Earning component calculated using the ROA ratio in 2017 it was 1.56 percent, in 2018 it was 0.93 percent, in 2019 it was 0.89 percent, in 2020 it was 1.74 percent and in 2021 it was 4.08 percent. In addition, the NIM ratio in 2017 was 6.03 percent, in 2018 it was 5.52 percent, in 2019 it was 5.36 percent, in 2020 it was 4.97 percent and in 2021 it was 4.35 percent. For the capital component calculated using the CAR ratio in 2017 it was 22.19 percent, in 2018 it was 20.54 percent, in 2019 it was 19.96 percent, in 2020 it was 24.15 percent and in 2021 it was 25.59 percent. From the results of the study, it is known that the ratio of ROA shows poor results.